2017
DOI: 10.3390/ijerph14050543
|View full text |Cite
|
Sign up to set email alerts
|

Is Neighborhood Green Space Protective against Associations between Child Asthma, Neighborhood Traffic Volume and Perceived Lack of Area Safety? Multilevel Analysis of 4447 Australian Children

Abstract: Heavy traffic is a source of air pollution and a safety concern with important public health implications. We investigated whether green space lowers child asthma risk by buffering the effects of heavy traffic and a lack of neighborhood safety. Multilevel models were used to analyze affirmative asthma cases in nationally representative cross-sectional data from 4447 children aged 6–7 years old in Australia. Case-finding was based upon a triangulation of affirmative responses to three questions on doctor-diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 51 publications
1
48
2
1
Order By: Relevance
“…Park prescriptions, despite these important and preliminary experimental evaluations, are still in a formative evaluation phase; there are many opportunities for research in this emerging practice. The theoretic basis for park prescriptions is derived from both observational and experimental studies that have demonstrated a health benefit to living near parks [14][15][16] or using parks [17,18]. Evidence that exposure to nature, presumably found in many parks, promotes health across the lifespan also bolsters the practice of park prescriptions [19][20][21][22].…”
Section: Ofmentioning
confidence: 99%
“…Park prescriptions, despite these important and preliminary experimental evaluations, are still in a formative evaluation phase; there are many opportunities for research in this emerging practice. The theoretic basis for park prescriptions is derived from both observational and experimental studies that have demonstrated a health benefit to living near parks [14][15][16] or using parks [17,18]. Evidence that exposure to nature, presumably found in many parks, promotes health across the lifespan also bolsters the practice of park prescriptions [19][20][21][22].…”
Section: Ofmentioning
confidence: 99%
“…Six studies were performed on birth cohorts; 18-23 6 had a cross-sectional design; 18,24-28 1 was an intervention study; 29 and 1 was a case-control study. 30 Twelve studies involved children of age 12 years, [19][20][21][22][23][24][25][26][27][29][30][31] and only two included children and adolescents. 18,28 Most of the studies were conducted in Europe, 19,23,24,27,30 2 in Australia, 21,25,26,28 4 in North America, 18,31 1 in Asia, 29 and 1 based on data from Swedish, Dutch, German, Australian, and Canadian birth cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…Преиму-ществами оценки FeNOex являются неинвазивный ха-рактер метода, простота повторных измерений и отно-сительно легкое использование. В то же время, требу-ются новые научные исследования, чтобы помочь кли-ницистам использовать и интерпретировать уровень фракции оксида азота в выдыхаемом воздухе (FENO) [1][2][3][4][5][6][7][8][9][10].…”
unclassified